2000
DOI: 10.1063/1.1329169
|View full text |Cite
|
Sign up to set email alerts
|

Gallium oxide as an insulating barrier for spin-dependent tunneling junctions

Abstract: Spin-dependent tunneling has been shown to occur through Ga 2 O 3 as the insulating tunnel barrier. Magnetic tunnel junctions of the type Co/Ga 2 O 3 /Ni 80 Fe 20 were prepared by oxidizing thin metal layer of Ga in oxygen plasma and characterized. The highest junction magnetoresistance observed was 18.2% at room temperature, increasing to 27.6% at 77 K. The average barrier height was estimated to be about 2 eV, as opposed to over 3 eV for junctions with Al 2 O 3 barrier of comparable quality. Otherwise these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
66
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(69 citation statements)
references
References 31 publications
(44 reference statements)
2
66
0
Order By: Relevance
“…[1][2][3][4][5] Recently, considerable effort has been devoted to the study of nanostructured ␤-Ga 2 O 3 because of the potential for applications in nanodevices. [6][7][8][9][10] In ambient conditions, monoclinic ␤-Ga 2 O 3 is the thermodynamically stable form and there are other four metastable structures: ␣-, ␥-, ␦-, and -Ga 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5] Recently, considerable effort has been devoted to the study of nanostructured ␤-Ga 2 O 3 because of the potential for applications in nanodevices. [6][7][8][9][10] In ambient conditions, monoclinic ␤-Ga 2 O 3 is the thermodynamically stable form and there are other four metastable structures: ␣-, ␥-, ␦-, and -Ga 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…The contribution from these channels grows with the number of thermally excited magnons, more so for the antiparallel (AP) configuration, with the consequent overall increase in conductivity and corresponding loss in TMR with increasing temperature [7,8]. In a different approach, Julliere's model was extended [9] to include both a temperature-dependent surface spin polarization, and a spin-independent current channel, assumed to arise from hopping within the barrier [10][11][12]. Other proposed mechanisms include barrier defect and/or magnetic impurity scattering [13][14][15][16] and band structure effects [17].…”
mentioning
confidence: 99%
“…The Ga 2 O 3 /GaAs interface seems to be robust. 3 It has been suggested that optimal tunneling properties may be found with thinner junctions and upon annealing 1,7 in ferromagnet/insulator/ferromagnet structures. This is due to competing effects, namely oxidation of the neighboring layers and the formation of metallic paths in the junction layer.…”
Section: Discussionmentioning
confidence: 99%
“…Ultrathin films of Ga 2 O 3 have attracted interest for use in applications including spin-dependent magnetic tunnel junctions 1 and compound semiconductor passivation. 2,3 Fabrication of these and similar Al 2 O 3 films has been accomplished by oxidation of metallic layers in air 4 and by plasma.…”
Section: Introductionmentioning
confidence: 99%